1991
DOI: 10.1128/jb.173.23.7582-7588.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genome conservation in isolates of Leptospira interrogans

Abstract: Reference strains for each of the 23 serogroups of Leptospira interrogans yielded different pulsed-field gel electrophoresis patterns of NotI digestion products. This was also the case for the 14 serovars belonging to serogroup Icterohaemorrhagiae (with one exception). The NotI restriction patterns of 45 clinical leptospiral isolates belonging to serovar icterohaemorrhagiae were analyzed and compared with those of type strains. No differences were observed between isolates from countries of different continent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
54
0
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 32 publications
(11 reference statements)
4
54
0
6
Order By: Relevance
“…Furthermore, the PFGE results identified the high clonality of isolates within the same serovars as described. 7,53,54 As mentioned earlier in this report, previous seroepidemiologic studies in the Philippines had detected antibodies against several Leptospira serovars such as Tarassovi, Sejroe, Poi, Javanica, Manilae, Losbanos, and Grippotyphosa in different human and animal serum samples. 1,[8][9][10][11][12][13][14][15][16]43 The antibodies detected in humans and animals in previous studies were also detected among the rats in our current study, which indicates that these serovars may have been present in the Philippines for several decades.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, the PFGE results identified the high clonality of isolates within the same serovars as described. 7,53,54 As mentioned earlier in this report, previous seroepidemiologic studies in the Philippines had detected antibodies against several Leptospira serovars such as Tarassovi, Sejroe, Poi, Javanica, Manilae, Losbanos, and Grippotyphosa in different human and animal serum samples. 1,[8][9][10][11][12][13][14][15][16]43 The antibodies detected in humans and animals in previous studies were also detected among the rats in our current study, which indicates that these serovars may have been present in the Philippines for several decades.…”
Section: Discussionmentioning
confidence: 70%
“…PFGE has shown that the genomes of leptospiral serovars are remarkably conserved, both over time and across wide geographical distribution [4][5][6]. Most but not all serovars gave unique PFGE patterns using the restriction enzyme NotI, although the L. interrogans serovar Copenhageni and Icterohaemorrhagiae were indistinguishable by NotI-PFGE [5,6]. These two serovars are also very difficult to distinguish by serological methods [11].…”
Section: Discussionmentioning
confidence: 99%
“…PFGE has been indicated to be a useful method for identification of leptospiral serovars [4][5][6]. PFGE has shown that the genomes of leptospiral serovars are remarkably conserved, both over time and across wide geographical distribution [4][5][6]. Most but not all serovars gave unique PFGE patterns using the restriction enzyme NotI, although the L. interrogans serovar Copenhageni and Icterohaemorrhagiae were indistinguishable by NotI-PFGE [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting restriction patterns are characteristic of a particular vaccine strain, and this information can be used to investigate the physical structure of the bacterial chromosome. 19,23 Reproducible PFGE profiles were found in 7 vaccine strains after in vitro and in vivo passage, further reflecting the genetic stability of leptospiral vaccine strains at the whole genome level. Previous studies have shown that repetitions of the same serovar consistently produced reproducible patterns, and the PFGE patterns of different strains of the same serovar are closely related.…”
mentioning
confidence: 98%